HIPERTENSI PADA DIABETES MELLITUS: SEBUAH TINJAUAN PUSTAKA - Heironimus Billy Febriyan; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Hypertension in patients with diabetes mellitus is a significant clinical problem because it increases the risk of cardiovascular and renal complications. The pathophysiology of this condition involves interactions between insulin resistance, activation of the renin–angiotensin–aldosterone system (RAAS), endothelial dysfunction, and oxidative stress, which trigger vasoconstriction, sodium retention, and increased vascular stiffness. Various clinical guidelines, including those of the American Diabetes Association (ADA), set a blood pressure target of <130/80 mmHg to reduce the risk of long-term complications. Evidence from clinical trials such as ABCD shows that intensive blood pressure control provides benefits in terms of the progression of retinopathy, albuminuria, and stroke risk. This article was compiled using a narrative review approach by examining the latest literature from international journals and clinical guidelines related to hypertension in diabetes. Sources were selected based on relevance, recency, and strength of evidence. The analysis was descriptive to summarize pathophysiology, blood pressure target recommendations, treatment options, and the role of lifestyle changes. Management of hypertension in diabetes requires a combination of pharmacological therapy and lifestyle modifications. ACE inhibitors and ARBs are the first choice due to their renal protective benefits, while calcium antagonists and thiazide diuretics are used as adjunctive therapy. Lifestyle interventions such as salt restriction, increased fruit and vegetable consumption, regular physical activity, weight loss, and alcohol restriction provide moderate blood pressure lowering effects and improve metabolic health. A comprehensive approach encompassing metabolic, pharmacological, and lifestyle management is crucial for reducing morbidity and mortality in patients with diabetes and hypertension.